High Mach Number Quasi‐Perpendicular Shocks: Spatial Versus Temporal Structure. Issue 9 (15th September 2021) - Omidi, N.; Desai, M.; Russell, C. T.; Howes, G. G.
Abstract: Planetary bow shocks are a natural laboratory for investigating the physics of collisionless shocks. Given that spacecraft observations provide us with information regarding the temporal structure of the shock, often multi‐spacecraft missions and kinetic simulations are needed to discern the nature of the dissipation processes at the shock and the resulting spatial structure. Such an approach through the ISEE mission and 1.5‐D hybrid (kinetic ions and fluid electrons) simulations led to an understanding of supercritical quasi‐perpendicular shocks. In such shocks, the reflection of a fraction of incident ions and their gyration back into the shock is part of the dissipation process resulting in the formation of a foot, ramp, overshoot, and undershoot. More recently, observations of high Mach number quasi‐perpendicular shocks show a seemingly turbulent structure in time series data. In this study, we use the results of 2.5‐D global hybrid simulation of a high Mach number quasi‐perpendicular shock to demonstrate the major differences between the spatial and temporal structure of such shocks. The spatial structure of the shock is the same as that of supercritical shocks while the temporal structure consists of fast magnetosonic pulses. The reason for this difference is attributed to the generation of surface waves at the shock which results in partial encounters between the shock and spacecraft. The surface waves are shown to be generated by large velocity shears present at the shock due to ion reflection and gyration into the upstream. Key Points: Hybrid simulation of a high Mach number quasi‐perpendicular shock shows a spatial structure consisting of a foot, ramp, and overshoot Using a simulated spacecraft, we show the same shock to have a seemingly turbulent temporal structure Major differences between spatial and temporal structure of the shock are observed due to the presence of surface waves